Electrospun TiC embedded CNFs as a low cost platinum-free counter electrode for dye-sensitized solar cell. (March 2016) - Saranya, K.; Subramania, A.; Sivasankar, N.; Mallick, S.
Graphical abstract: Highlights: TiC–CNFs by electrospinning technique to use as CE for DSSC applications. TiC–CNFs exhibits better electrocatalytic activity and low R ct for I3 – reduction. The PCE of DSSC with TiC–CNFs as CE was very closer compared to std. Pt. Abstract: Generally, platinum (Pt) is used as a counter electrode (CE) for triiodide (I3 − ) reduction in the electrolyte solution of dye-sensitized solar cell (DSSC). Unfortunately, the high cost and scarcity of Pt make the limitation for large scale production of DSSCs. Hence, to replace Pt, we have prepared the titanium carbide (TiC) embedded carbon nanofibers (CNFs) by a facile electrospinning technique and used as a low cost alternative CE for DSSCs. The TiC embedded CNFs are found to have an enhanced electrocatalytic activity towards the I3 – to iodide (I – ) reduction and lower charge transfer resistance. The photovoltaic performance shows that the DSSC fabricated using TiC (10 wt%) embedded CNFs as CE has very closer photo-conversion efficiency than std. Pt. This is attributed to the synergistic effect of TiC with larger electrocatalytic surface area of CNFs which plays a substantial part in the improvement of photovoltaic performance of DSSC.